Exploring Pre-Service Teachers' Difficulties of ChatGPT as a Tool for Planning The Learning Process - Dimas, Dimas; Alvindi, Alvindi; Khoirunnisa, Tengku; Yani, Rahma; Pardamean, Pardamean; Simanjuntak, Khoirunnisa (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate the challenges faced by pre-service teachers in using ChatGPT as a tool for planning the learning process. Despite the potential of ChatGPT to enhance efficiency, creativity, and innovation in educational contexts, its implementation among pre-service teachers remains limited due to a range of difficulties. These include challenges in formulating learning objectives, selecting appropriate teaching methods and tools, and assessing the relevance of AI-generated content to curriculum standards. Using a quantitative research approach, a survey was conducted with 30 pre-service teachers in North Sumatra, Indonesia, to explore the barriers encountered across the planning, implementation, and evaluation phases of the learning process. Findings indicate that while ChatGPT offers valuable support, pre-service teachers experience moderate to high levels of difficulty in critical areas such as identifying relevant resources, structuring learning activities, and facilitating effective student engagement. These challenges underscore the need for targeted training and pedagogical support to optimize the integration of AI tools in teacher education programs. The study provides insights into the complexities of adopting AI in education and proposes strategies for overcoming these barriers, contributing to the discourse on technology-enhanced learning in developing educational contexts.